Quality Care Questionnaire-palliative Care: tradução, adaptação transcultural e validação para o português brasileiro em pacientes com câncer - BARROS, Vinício dos Santos (2020)
Objective: To translate, cross-cultural adapt and validate the Quality Care Questionnaire-Palliative Care (QCQ-PC) into Brazilian Portuguese in cancer patients in palliative care. Materials and methods: This study was carried out in the Pain and Palliative Care sector of the Hospital do Câncer do Maranhão (São Luís, MA, Brazil), and was approved by the Research Ethics Committee of the Federal University of Maranhão (consubstantiated opinion number 2.984.884). The process of translation and cross-cultural adaptation of the QCQ-PC into Brazilian Portuguese followed international criteria, with the following stages: translation, synthesis of translations, backtranslation, analysis by experts committee, testing of the pre-final version and definition of the final version. Participants were cancer patients diagnosed by biopsis and aware of his/her diagnosis, 18 years old or older, of both genders and able to read and understand Brazilian Portuguese. The psychometric properties evaluated were: structural validity by means of exploratory and confirmatory factor analysis; test-retest reliability by means of intraclass correlation coefficient (ICC), internal consistency by means of Cronbach’s alpha, construct validity by means of correlations between QCQ-PC and European Organization for Research in the Treatment of Cancer Questionnaire-core (EORTC- QLQ-C15-PAL), McGill Quality of Life Questionnaire (MQOL), Barthel Index, Edmonton Symptom Assessment System (ESAS), calf circumference, Karnofsky Performance Scale (KPS) and Palliative Prognostic Index (PPI). Results: Two hundred and twenty-five cancer patients were included for validity analyzes, and a subsample of 30 patients was used for test-retest reliability. For structural validity, shorted version of the QCQ-PC, with two domains and 12 items showed more adequate fit indexes than original version. In the reliability analysis, each item of the QCQ-PC demonstrated adequate kappa values (≥0.37). For the total score, QCQ- PC showed adequate reliability (ICC ≥0,77 and SEM ≤ 9,26%) and internal consistency (Cronbach's alpha ≥ 0.78) Regarding the construct validity, correlations greater than 0.30 were observed between QCQ-PC and KPS, PPI, sadness domain of ESAS, Barthel Index and all domains related to the quality of life of MQOL and EORTC-QLQ-C15-PAL. Discussion: Patient satisfaction with the assistance provided by health professionals is an important self-reported measure in palliative care, because it is highly correlated with quality of life. Understanding patient satisfaction with health assistance allows the health professionals to implement actions to provide maximum comfort during palliative care. Conclusion: The Brazilian version of the QCQ-PC with two domains and 12 items has acceptable psychometric properties and can be used in cancer patients in palliative care.